Solitary Fibrous Tumor of the Lumbar Spine: The Great Mimicker—Report of the Fifth Case - Amer Sebaaly; Lara Raffoul; Ronald Moussa (Case Reports in Orthopedics)
Solitary fibrous tumor (SFT) is a rare neoplasm occurring in the central nervous system. It rarely occurs in the spine. This paper reports the fifth case of SFT in a 34-year-old female and focusses on differential diagnosis and importance of surgical treatment.